The influence of employee productivity and service quality of front office department on job satisfaction mediated by work motivation in the hospitality sector - Pujiati, Rina; Nainggolan, Romauli; Sarwoko, Endi (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
This study focuses on how staff productivity and service quality of the front office department affect job satisfaction, with work motivation as a mediating variable in the hospitality sector The objectives are to determine how employee productivity affects job satisfaction, evaluate how service quality affects job satisfaction, and examine how work motivation functions as a mediating factor among productivity, service quality, and job satisfaction. Front desk staff at a number of Indonesian hotels completed a questionnaire with a Likert scale of 1–5, which was used to gather data using quantitative methods. Job satisfaction, work motivation, service quality, and employee productivity were among the variables examined. Data analysis was conducted using SEM-PLS (Structural Equation Modeling-Partial Least Squares) in Smart-PLS statistical software. Validity and reliability testing were also conducted to make sure the study tool was suitable. The analysis on the 79 responses collected via google forms revealed that while job satisfaction is less significantly impacted, employee productivity and service quality have a considerable impact on work motivation. It is discovered that work motivation plays a significant part in raising job satisfaction.